PD-1 Affects the Immunosuppressive Function of Group 2 Innate Lymphoid Cells in Human Non-Small Cell Lung Cancer - Shen, Chunyi; Liu, Chaojun; Zhang, Zhen; Ping, Yu; Shao, Jingwen; Tian, Yonggui; Yu, Weina; Qin, Guohui; Liu, Shasha; Wang, Liping; Zhang, Yi (Frontiers in Immunology, 2021)
Background: There is increasing evidence that group 2 innate lymphoid cells (ILC2s) play an essential role in allergy and parasitic infection. However, the role of ILC2s in human lung cancer remains unclear. Methods: ILC2s from peripheral blood mononuclear cells (PBMCs) obtained from healthy donors (HDs) and non-small cell lung cancer (NSCLC) patients, and NSCLC tumor tissues were analyzed via multicolor flow cytometry. ILC2s or CD14+ cells were sorted by fluorescence-activated cell sorting. qPCR and flow cytometry were performed to assess the gene and protein expression of the indicated molecules. M1-like and M2-like macrophages were induced from CD14+ monocytes in vitro. Results: ILC2s were significantly more enriched in PBMCs and tumor tissues from NSCLC patients than in HDs. After screening for the main immune checkpoint molecules, we found that PD-1 was upregulated in ILC2s in NSCLC patients. Functionally, PD-1high ILC2s from tumor tissues expressed higher levels of IL-4 and IL-13 regarding both mRNA and protein levels than PD-1low ILC2s. Furthermore, PD-1high ILC2s robustly boosted M2-like macrophage polarization in vitro, by secreting IL-4 and IL-13, while neutralization of IL-4 and IL-13 by antibodies abrogated M2-like macrophage polarization. Conclusion: ILC2s are enriched in NSCLC patients and upregulate PD-1 expression. Upregulation of PD-1 facilitates the immunosuppressive function of ILC2s. PD-1high ILC2s enhance M2-like macrophage polarization by secreting IL-4 and IL-13. PD-1 acts as a positive regulator of the immunosuppressive function of ILC2s in human NSCLC.